Mosquito Repellent Bioactivity Combination Extract Of Nutmeg Leaf (Myrisctica fragrans Houtt), Lemongrass (Cymbopogon nardus L.) and Apis dorsata Binghami Nests - Meisa Tabita Rogahang; Orbanus Naharia; Yermia Semuel Mokosuli (Jurnal Biologi Tropis, 2023)
Nutmeg leaf, lemongrass, and bee nests contain bioactive compounds that have potential as mosquito repellents. The purpose of this study was to learn about the bioactivity of a combination extract of nutmeg leaf, lemongrass, and bee nests, as well as to determine the efficient mosquito repellent lotion recipe from a combination of nutmeg leaf, lemongrass, and bee nests extract. The maceration process was used for extraction. Total flavonoid content was estimated by comparing it to the flavonoid quercetin. The absorbance value was measured with a UV-Vis spectrophotometer. The concentration of the extract combination in the lotion used was 0%, 2.5%, 5% and 10%. The total flavonoid concentration was found to be 16.67 mgQE/g. The 2.5% formula lotion has a protective power of 22%, the 5% formula lotion has a power of 62.96%, and the 10% formula lotion has a power of 82.41%. From these results, it can be seen that a formula with a concentration of nutmeg leaf, lemongrass, and bee nests as much as 10% can be the most effective mosquito repellent. The outcomes of this study are expected to help the community select environmentally friendly and safe insect repellents.